Cortisol and behavioral reaction of low and high sensation seekers differ in responding to a sport-specific stressor. Issue 5 (3rd September 2018) - Frenkel, Marie Ottilie; Heck, Robin-Bastian; Plessner, Henning
ABSTRACT: Background/objectives: Sensation seeking is closely related to practicing high-risk sports. This domain offers individuals an opportunity to achieve an increased level of arousal. Moreover, stress reactivity implies interindividual differences in the capacity to respond to a stressor. The purpose of this study was to examine whether high sensation seekers (HSS) compared to low sensation seekers (LSS) experience lower levels of stress on a physiological and psychological basis. Stress was induced in a sport-specific experimental paradigm with a climbing task through a jump into the rope. Methods: Two extreme groups ( n = 28 male athletes) were examined in a mixed-factorial design ( between : HSS vs. LSS; within : repeated measurements of several variables related to stress reactivity - cortisol, heart rate, anxiety). Results: In response to the stressor HSS compared to LSS released a significantly lower amount of cortisol and needed less time for the climbing task. Heart rate and anxiety were not significant. Conclusions: Individuals seem to react physiologically differently to a sport-specific stressor, depending on their level of sensation seeking. HSS seem to be less strained, and seem to perform better. These findings might be relevant not only for the evaluation of (sport-) psychological interventions but also for other contexts (e.g., special forces).